An Extension of the Truncated-Exponential Skew- Normal Distribution - Pilar A. Rivera; Diego I. Gallardo; Osvaldo Venegas; Marcelo Bourguignon; Héctor W. Gómez (Mathematics, 2021)
In the paper, we present an extension of the truncated-exponential skew-normal (TESN) distribution. This distribution is defined as the quotient of two independent random variables whose distributions are the TESN distribution and the beta distribution with shape parameters q and 1, respectively. The resulting distribution has a more flexible coefficient of kurtosis. We studied the general probability density function (pdf) of this distribution, its survival and hazard functions, some of its properties, moments and inference by the maximum likelihood method. We carried out a simulation and applied the methodology to a real dataset.